Monitoring MCS patients on the intensive care unit: integrating haemodynamic assessment, laboratory data, and imaging techniques for timely detection of deterioration and recovery - Vandenbriele, Christophe; Baldetti, Luca; Beneduce, Alessandro; Belohlavek, Jan; Hassager, Christian; Pieri, Marina; Polzin, Amin; Scandroglio, Anna Mara; Møller, Jacob Eifer (European heart journal supplements, 2023)
Monitoring of the patient supported with a temporary mechanical circulatory support (tMCS) is crucial in achieving the best possible outcome. Monitoring is a continuous and labour-intensive process, as cardiogenic shock (CS) patients can rapidly deteriorate and may require new interventions within a short time period. Echocardiography and invasive haemodynamic monitoring form the cornerstone of successful tMCS support. During monitoring, it is particularly important to ensure that adequate end-organ perfusion is achieved and maintained. Here, we provide a comprehensive overview of best practices for monitoring the CS patient supported by a micro-axial flow pump, veno-arterial extracorporeal membrane oxygenation, and both devices simultaneously (ECMELLA approach). It is a complex process that encompasses device control, haemodynamic control and stabilization, monitoring of interventions, and assessment of end-organ function. The combined, continuous, and preferably protocol-based approach of echocardiography, evaluation of biomarkers, end-organ assessment, and haemodynamic parameters is crucial in assessing this critically ill CS patient population.